B cell epitopes of the heterogeneous nuclear ribonucleoprotein A2: identification of a new specific antibody marker for active lupus disease. Issue 5 (21st May 2008) - Schett, G; Dumortier, H; Hoefler, E; Muller, S; Steiner, G
Abstract : Objectives: Autoantibody formation and T cell reactivity against the heterogeneous nuclear ribonucleoprotein A2 (hnRNP-A2) has been observed in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Since no differences in epitope recognition were reported and the usefulness of anti-hnRNP-A2 antibodies as diagnostic markers of SLE is unknown, it was our objective to characterise linear B cell epitopes of hnRNP-A2 and to relate the anti-hnRNP-A2 antibody responses to disease activity and clinical features of SLE. Methods: Sequential serum samples from 15 patients with SLE and sera from patients with other rheumatic diseases and healthy subjects were investigated by ELISA for autoantibody reactivities against a set of 13 overlapping peptides spanning the RNA-binding region of hnRNP-A2. Antibody reactivity against the complete protein was determined by western immunoblotting and ELISA. SLE disease activity was assessed by European Consensus Lupus Activity Measure scores, by SLE Index scores and the British Isles Lupus Assessment index. Results: Anti-peptide antibody reactivities were found in 60% of SLE sera but in only 5% of control samples, and were mainly directed to four peptides, one of which (p155–175) appeared to be immunodominant. Antibodies to p155–175 were exclusively seen in patients with SLE and correlated with clinical disease activity as well as kidney and skin involvement. No correlations were found for the other anti-peptide antibody responses. Conclusion: Peptide p155–175 encompasses a disease-specific immunodominant epitope of hnRNP-A2. Since antibodies to p155–175 correlate with disease activity and nephritis, they may be useful as markers for active SLE.